Mechanisms Underlying the Anti-inflammatory Effects of the Ca2+/Calmodulin Antagonist CV-159 in Cultured Vascular Smooth Muscle Cells - Tatsuya Usui; Hideyuki Yamawaki; Masato Kamibayashi; Muneyoshi Okada; Yukio Hara (Elsevier, 2010)
CV-159 is a unique dihydropyridine Ca2+antagonist with an anti-calmodulin (CaM) action. A pathogenic feature of atherosclerosis is vascular inflammatory change. In the present study, we examined whether CV-159 exerts protective effects on smooth muscle inflammatory responses. After pretreatment of rat mesenteric arterial smooth muscle cells (SMCs) with CV-159 (0.1 - 10 μM, 30 min), TNF-α (10 ng/ml) was applied for 20 min or 24 h. CV-159 inhibited TNF (24 h)-induced vascular cell adhesion molecule (VCAM)-1 as determined by Western blotting. CV-159 inhibited TNF (20 min)-induced phosphorylation of Akt (Ser473) and NF-κB p65 (Ser536). An Akt inhibitor, LY294002, and an NF-κB inhibitor, pyrrolidine dithiocarbamate, inhibited TNF-induced VCAM-1. An antioxidant drug, N -acetyl-l-cysteine (NAC) inhibited TNF-induced VCAM-1. NAC also inhibited TNF-induced phosphorylation of Akt and NF-κB. Furthermore, CV-159 inhibited TNF-induced reactive oxygen species (ROS) production as determined fluorometrically using dichlorodihydrofluorescein diacetate. A CaM inhibitor, W-7, and a calcium/ CaM-dependent protein kinase type II inhibitor, KN93, inhibited TNF-induced VCAM-1. W-7 and KN93 inhibited TNF-induced phosphorylation of Akt but not NF-κB. The present results indicate that in vascular SMCs, CV-159 inhibits TNF-induced VCAM-1 through inhibition of NF-κB and Akt phosphorylation. CV-159 prevents NF-κB phosphorylation by inhibiting ROS, while it prevents Akt phosphorylation by inhibiting both ROS and CaM. Keywords:: dihydropyridine derivative, vascular smooth muscle, inflammation, signal transduction, calmodulin